Why we need to reimagine the curricula in higher education to make it more culturally sensitive. (9th December 2021) - Thomas, Dave; Quinlan, Kathleen
Persistent racial equality gaps exist in HE. We argue that culturally sensitive curricula can address those racial equality gaps as well as support the development of culturally competent graduates equipped for social change. In this short piece, we briefly describe our conceptualisation of culturally sensitive curricula and the tool we have developed to support curricular enhancement. We report on emerging evidence of the impact of culturally sensitive curricula on students' engagement and suggest how such curricula could lead to impact on educational outcomes.